Desarrollo nutricional y su aporte en el desempeño académico de los estudiantes de 2° año de educación general básica de la Unidad Educativa del Milenio Carmelina Granja Villanueva Parroquia San Carlos, Cantón Quevedo, provincia de los Ríos. - Franco Chica, Jacqueline Lisseth (2021)
Eating habits are established during childhood that will later be difficult to change. With proper eating and lifestyle habits, we contribute positively to building and shaping your body and improving your health, physical performance, and academic performance. A correct diet during childhood is important, because the child's body is growing and forming, which is why it is more vulnerable to any nutritional problem. A healthy and balanced diet is essential for the health status of children, and a determining factor for a proper functioning of the body, good growth, an optimal ability to learn, communicate, think, socialize and adapt to new environments and people, a correct development psychomotor and ultimately for the prevention of risk factors that influence the appearance of some diseases. Good nutrition is the first line of defense against many childhood illnesses that can leave their mark on children for life. The effects of malnutrition in early childhood (0 to 8 years) can be devastating and long-lasting. They can impede behavioral and cognitive development, school performance, and reproductive health, thereby undermining future productivity at work.